Special temperatures in frustrated ferromagnets - L. Bovo (Nature Portfolio, 2018)
Competing interactions in frustrated magnets give rise to complex emergent phenomena, which challenge a full microscopic understanding but invite comparison to other systems. Bovo et al. find an analogy to classical gases and identify special temperatures that reveal fine details of the microscopic Hamiltonian.